Bioprospecting and Diversity of Yeast Producing Ethanol Isolated from Indonesia - Eny Ida Riyanti; Rafika Yuniawati; Edy Listanto (Tropical Life Sciences Research, 2022)
Bioethanol is considered the most environmentally friendly as renewable fuels. Indonesia has abundant microbe diversity which is potential for bioprospecting such as fermenting agents using agriculture product as raw materials for producing bioethanol. This study aims to isolate, characterise and molecular identify of 15 isolates of bioethanol- producing yeasts from various sources. Characterisation based on ethanol production, cell morphology and various substrate utilisation has been carried out. Molecular characterisation of 15 yeast isolates using tree sets of primers had been carried out. Amplification in the internal area of transcribe spacers (ITS) was successfully carried out with an amplitude of 400 bp–900 bp. Amplifiers in the D1/D2 26s rDNA domain are 250 bp. Amplification with ScerF2 and ScerR2 specific primers was carried out successfully and proved that there were two isolates which were not Saccharomyces cerevisiae analysis of yeast genetic diversity showed 12 yeast isolates classified as S. cerevisiae and the rest belonged to the genus Clavispora, Candida and Kodamaea (Pichia).